Exploring the Level of Knowledge of Patients Regarding Antibiotics Use in AL- Najaf City Hospitals, Iraq - Bazma, Anwer Kadhim; Fareed, Abdul-Ameer Ali; Ahmed, Jabbar Taresh (American Journal of Biomedicine and Pharmacy, 2025)
Background: Antibiotics are drugs that either kill or stop the growth of bacteria in order to treat bacterial infections. Because misuse can result in bacterial resistance, which makes treating infections more challenging, they should be used carefully. Objective: This study seeks to assess the level of knowledge of patients regarding antibiotics use. Methodology: cross-sectional study was conducted in selected government hospitals in Al-Najaf city from 1 October 2024 until the end of January 2025 to assess the knowledge of patients regarding antibiotic use. Data were collected from 400 patients using a structured questionnaire and analyzed using SPSS-27. Results: the results of this study indicate that 61.8% of patients have a fair knowledge score, followed by 23.0% of the participants have a good knowledge score, and only 15.2% of patients have a poor knowledge score. The results of this study reveal that there is a significant relationship between demographic characteristics (such as age groups, residence, gender, marital status, educational level, high professional occupation and socioeconomic status) and overall knowledge score (P. value <0.05). Conclusion: The study conclude that more than half of patients have moderate level of knowledge about antibiotic use. The study found that young age, female gender, single, those live in urban areas, high professional occupation, high socio-economic status and high education patients, have good assessment scores for knowledge about antibiotic at significantly level <0.05.